Proinflammatory and anti-inflammatory cytokines in meningococcal disease. Issue 5 (November 1996) - Riordan, F A; Marzouk, O; Thomson, A P; Sills, J A; Hart, C A
Abstract : Interleukin-10 (IL-10), an anti-inflammatory cytokine, was measured in 131 children with meningococcal disease. IL-10 concentrations were significantly higher in children who died and correlated positively with proinflammatory cytokines. Children who die from meningococcal disease have high IL-10 concentrations, which do not suppress proinflammatory cytokines.